TRANSLATION STRATEGIES OF THE JAMAICAN DIALECT IN HOUCK'S NOVEL 'TIGER'S VOYAGE' - Victoria Yunita; Sukarno; Riskia Setiarini (UIN Raden Mas Said Surakarta, 2022)
Dialects in literary works give new challenges for translators. In the novel Tiger’s Voyage, one character with Jamaican English dialect is presented differently by the way of his speaking, so is in the Indonesian translation. This research aimed to analyze the translation strategies used for translating the dialects in Indonesian translation based on Berezowski’s dialectical translation strategies. This study applies qualitative method by utilizing data in the forms of dialogues spoken by the character. The result shows that six out of ten translation strategies were applied with artificial variety as the most dominant one. The application of the strategies was based on the phonological and syntactic deviation existing in the data, from which the Indonesian translator choses to keep the phonological deviation as the only modification remains. As an implication, the Indonesian translation of Tiger’s Voyage stays allegiant to the source text where Jamaican English dialect is presented through the character, even though it is made artificially. Through the modifications, however, the translation can still be comprehended by the target text readers. It is adjusted to the target language by adhering to domestication technique to anticipate the readers from confusion.